High quality liquid crystal displays and smart devices. Volume 1, - Ishihara, Shoichi; Kobayashi, Shunsuke; Ukai, Yasuhiro (Materials, circuits and devices series ;, 2019)
The book deals with the following topics:- History of LCD: milestone, state-of-the-art and future directions; In-plane switching technology; Fringe-field switching technology; Vertically aligned liquid crystal display; Evolving LCD-TV technology; Picture performance evolution for the high dynamic range era; TFT-LCD and AMOLED display technology comparisons; Automotive displays; Requirements for automotive displays; The world's largest curved LCD; Optical design of flexible liquid crystal displays; Flexible LCD; Film substrate for flexible devices; Thin film transistors for active-matrix LCDs; Ultrahigh-resolution LCDs with oxide semiconductor TFTs; Oxide semiconductors for display applications; Liquid crystalline organic semiconductors; Liquid crystal materials; Quantum dot technology and its applications; and Backlighting unit optics: optical micro-reflectors and micro-deflectors for functional light-guide plate.